The effect of restricted feed on feed intake, egg production and feed conversion in pullets - Cerci, IH; Tath, P; Azman, MA; Birben, N (Indian Veterinary Journal, 2003)
Different methods have been applied for increasing production in layer pullets. One the methods is restricted (Kwakkel et al., 1995; Ergul et al., 1992). Bainave (1973) reviewed the methods of restricting nutrient intake-during growth for improved. subsequent performance of layer-type pullets; Advantage of quantitative feed restriction and limited time feeding over the nutrient restriction method is that a special. feed formulation is not necessary (Reddy, 1992). The purpose of this study was to evaluate production of layer-type pellets with restricted feed under heat stress.
Keywords: Body-Composition; Leghorn Pullets; Hens; Growth; Energy